Market Survey of Fresh and Marine Water Fishes and Socioeconomic Conditions of Fish Retailers in Three Markets of Chattagram City (Bangladesh Journal of Zoology, 2021)
The study was carried out to survey the fresh and marine water fishes sold out in three markets of Chattagram city and socioeconomic condition of the fish retailers. Overall 29 fresh water and 24 marine water fish species were found to be sold in the three markets. Prices of fishes were higher in Kazirdewri Bazar followed by Riazuddin Bazar and Bohaddarhat Bazar. Data of fish retailers were collected through questionnaires in terms of age, income source, living standards, family size, financial facilities, literacy and education. Sole income came from fish business for 97% of the fish retailers, whilst 3% of the retailers did other business as well. Among 45 retailers interviewed, 40% were below 45 years, 53% were between 45-55 years and remaining 7% were above 55 years age. For coping with the business, 15% of the retailers were self-sufficient, 53% took loan from bank, whilst 32% took loan from local money lenders. Of the fish retailers, 34% was illiterate and 66% was literate, where 36% received up to primary level, 16% secondary level, 10% S.S.C and 4% H.S.C levels of education. In comparison with their education status their children were more educated (93%). Although their income was low, they tried to make their children educated, which is a good sign for our education sector. Transport cost, unhygienic market place, lack of sanitary facilities, poor ice-supply, exploitation by the middlemen, lack of proper management, lack of capital and the political disturbances were the common constraints of fish marketing. Necessary measures were recommended to overcome these problems.Bangladesh J. Zool. 49 (2): 277-288, 2021